2021
DOI: 10.1371/journal.pone.0254658
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of microorganisms associated with automated teller machines on Federal Polytechnic Ede campus

Abstract: Automated Teller Machines (ATM) are visited everyday by millions of people. This machine is accessible to the general public irrespective of class, age or race. The contact point of all ATM machines is the hand which on their own are ‘vaults’ of microorganisms. An elaborate survey was taken for complete assessment of possible microbial contamination in the Federal Polytechnic Ede campus. Selected ATM machines on campus were used as case study to characterize, identify and determine the degree of bacterial cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 41 publications
2
4
0
Order By: Relevance
“…This study reveals significant bacterial contamination of fomites in all the three facilities, with Gram-positive bacteria (71.9%) being isolated more frequently than Gram-negative bacteria (28.1%). The increased predominance of Grampositive bacteria over Gram-negative bacteria is consistent with prior research and corroborates the assertion that Grampositive bacteria outnumber Gram-negative bacteria as the primary group of bacteria recovered from fomites [18,19]. This observation is due to the fact that Gram-positive bacteria are a natural part of both healthy and sick people's body flora and can be spread by hand, respiratory tract, or contact with animate or inanimate objects [20].…”
Section: Discussionsupporting
confidence: 88%
“…This study reveals significant bacterial contamination of fomites in all the three facilities, with Gram-positive bacteria (71.9%) being isolated more frequently than Gram-negative bacteria (28.1%). The increased predominance of Grampositive bacteria over Gram-negative bacteria is consistent with prior research and corroborates the assertion that Grampositive bacteria outnumber Gram-negative bacteria as the primary group of bacteria recovered from fomites [18,19]. This observation is due to the fact that Gram-positive bacteria are a natural part of both healthy and sick people's body flora and can be spread by hand, respiratory tract, or contact with animate or inanimate objects [20].…”
Section: Discussionsupporting
confidence: 88%
“…placed and also on the microbial flora of the human handling them. Similar bacteria were reported on lids of beverage cans (Michaels et al, 2003), other inanimate objects such as keyboards mobile phones (Koscova, Hurnikova, & Pistl, 2018), ICU equipments (Nazeri et al, 2019) and Automated Teller Machines ATM (Dawodu & Akanbi, 2021).…”
Section: Cleaning Experimentssupporting
confidence: 65%
“…44,45,46,47], and also identified by other researchers on ATM surfaces [e.g. 3,4,5,6,7,8,9,10,11]. Analysis of percentage contribution showed that the dominant groups of microorganisms, both on the examined surfaces and in the air, were Gram-positive cocci and filamentous fungi.…”
Section: Microbiological Contamination Of the Air In Premises Housing...mentioning
confidence: 56%